Psychological effects produced by the covid-19 pandemic on children from 8 to 9 years old, of the bilingual private school Pelileo (Horizontes de Enfermería, 2021)
The present research aimed to identify the psychological effects produced by the COVID-19 pandemic on children aged 8 to 9 years of the Pelileo Bilingual Private School. For which aquantitative study was developed, based on a cross-sectional field research, with a descriptive level, considering the population under study were infants from 8 to 9 years of age, from the educational institution in mention, the sample was determined by inclusion criteria such as age range, students of the institution and those who wish to participate in the research, excluding those who did not comply with these selection items, for which a sample of 28 students wereobtained. A survey based on the Child Anxiety Questionnaire (CAS) and the Child Depression Questionnaire (CDI) was applied as a data collection instrument, which after being applied and processed, resulted in the presence of anxiety syndrome in 78.57% of the child population, who presented associated signs, avoidance of responsibilities, increased anger, nervousness, feeling of dependency and withdrawal. Likewise, the presence of depression syndrome was identified in 100% of children. Which is divided into a mild level in 64.29% of cases and a serious condition in 35.71%. Establishing recommendations that improve the mental health of children such as promoting dialog with parents, and creating routines that include physical activities such as rumba therapy.
Keywords: Psychological Effects; Mental Health; Pandemic; Anxiety; Depression